2021
DOI: 10.7717/peerj.11100
|View full text |Cite
|
Sign up to set email alerts
|

Warming resistant corals from the Gulf of Aqaba live close to their cold-water bleaching threshold

Abstract: Global climate change is causing increasing variability and extremes in weather worldwide, a trend set to continue. In recent decades both anomalously warm and cold seawater temperatures have resulted in mass coral bleaching events. Whilst corals’ response to elevated temperature has justifiably attracted substantial research interest, coral physiology under cold water stress is relatively unfamiliar. The response to below typical winter water temperature was tested for two common reef building species from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 63 publications
4
10
0
Order By: Relevance
“…Moreover, S. pistillata systematically showed the strongest decrease in photophysiological performances as a result of elevation of temperatures (trend visible on Figs 2 and 3 ), but more replicates are needed to characterize this species as the most sensitive. A recent study reported that S. pistillata from the GoA may be living close to its cold-water bleaching threshold ( Bellworthy and Fine, 2021 ), which together with our results may suggest that S. pistillata is going through a population-level selection (i.e. adaptation) to the cooler waters of the GoA and may be subsequently losing its high thermal resistance compared to other common reef-building species.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Moreover, S. pistillata systematically showed the strongest decrease in photophysiological performances as a result of elevation of temperatures (trend visible on Figs 2 and 3 ), but more replicates are needed to characterize this species as the most sensitive. A recent study reported that S. pistillata from the GoA may be living close to its cold-water bleaching threshold ( Bellworthy and Fine, 2021 ), which together with our results may suggest that S. pistillata is going through a population-level selection (i.e. adaptation) to the cooler waters of the GoA and may be subsequently losing its high thermal resistance compared to other common reef-building species.…”
Section: Discussionsupporting
confidence: 78%
“…GoA corals, sampled in colder ambient conditions (22°C) compared to the GoT (28°C), may be more sensitive to higher irradiance at low temperature. Indeed, lower seawater temperatures have recently been shown to impair the photosynthetic efficiency of algal symbiont in GoAheat-tolerant corals ( Bellworthy and Fine, 2021 ; Marangoni et al ., 2021 ). RLCs at each temperature tested would help understand the temperature-specific response of the coral holobiont under increasing light irradiance.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the Bouraké lagoon is mostly N-limited (DIN : DIP < 10 and Si(OH) 4 : DIN > 1), which confirms the findings of Justić et al (1995) and is similar to the conditions observed in other New Caledonian mangroves (Jacquet et al, 2006). Nutrient limitation has been demonstrated to lower the temperature effect at which coral bleaching occurs (Wiedenmann et al, 2013;Ezzat et al, 2016aEzzat et al, , 2019, which contrasts with the resilience of Bouraké corals to the warming in the summer of 2016 (10 %-20 % bleaching only) compared to other reefs in New Caledonia (up to 90 % bleaching) (Benzoni et al, 2017). Coral symbionts recycle their host's metabolic wastes and take up dissolved inorganic nitrogen (DIN) and phosphorus (DIP) from seawater (Grover et al, 2003;Pernice et al, 2012;Rosset et al, 2015), both of which are used to produce vital organic molecules.…”
Section: Effects Of Physical and Chemical Conditions On Species Distributionsupporting
confidence: 85%
“…3), but it is also colder during winter, resulting in an annual temperature range of 17.5-33.8 • C. We compared temperatures recorded at Bouraké lagoon to those of the reference St R2, which showed the most typical temperature range for shallow water temperatures in the south of New Caledonia (i.e., 22-28 • C; Varillon et al, 2021). We notice that in Bouraké, temperatures were 40 % of the time above 28 • C during the summer of 2020, while winter temperatures were on average 46.5 % of the time lower than 22 • C. While warming is considered the main threat for coral reefs, low temperatures (< 20 • C) can cause coral bleaching by inducing responses similar to high F. Maggioni et al: The Bouraké semi-enclosed lagoon (New Caledonia) temperatures, including a reduction in the Symbiodiniaceae cell density and chlorophyll a content (e.g., Saxby et al, 2003;Hoegh-Guldberg and Fine, 2004;Hoegh-Guldberg et al, 2005;Kemp et al, 2011;Bellworthy and Fine, 2021). The negative effect of cold temperatures is even more substantial during neap tides when colonies on the reef crest are exposed to air for hours at low temperatures during cold winters.…”
Section: Physical and Chemical Characteristics Of The Bouraké Lagoonmentioning
confidence: 99%
“…If we compare temperature recorded at the reference St R2, which showed the most typical temperature range for shallow water temperatures in the south of New Caledonia (i.e., 22 -28 °C, (Varillon et al, 2021), we notice that in Bouraké temperatures were 40% of the time above 28°C during the summer of 2020, while winter temperatures were on average 46.5 % of the time lower than 22 °C. While warming is considered the main threat for coral reefs, low temperatures (< 20 °C) can cause coral bleaching by inducing responses similar to high temperatures, including a reduction in the Symbiodiniaceae cell density and chlorophyll a content (e.g., Saxby et al, 2003;Hoegh-Guldberg and Fine, 2004;Hoegh-Guldberg et al, 2005;Kemp et al, 2011;(Bellworthy and Fine, 2021). The negative effect of cold temperatures is even more substantial during neap tides when colonies on the reef crest are exposed to air for hours at low temperatures during cold winters.…”
Section: Physical and Chemical Characteristics Of The Bouraké Lagoonmentioning
confidence: 99%